An Optimized MicroPET Imaging Method for the Distribution and Synergies of Natural Products - Cui, Qingxin; Liu, Yang; Zhou, Mengge; Han, Yanqi; Yin, Chengcheng; Bai, Gang (Frontiers in Pharmacology, 2018)
Purpose: Understanding the distribution and interaction of the traditional Chinese medicines (TCMs) is an integral facet of herbal drug discovery. We report an optimized radio-labelled method that could conduct biodistribution studies in situ at the animal level in vivo. Viability of the method has been evaluated analytically and applied using glycyrrhetic acid (GA) and Platycodon grandifloras (PG) polysaccharides as a model. Procedures: [18F]-GA is a novel radiotracer which was performed whole-body positron emission tomography (PET) studies in mice to evaluate the biodistribution and dosimetry of GA. In addition, PG polysaccharides was used to intervene the biodistribution and dosimetry of GA. Data were analyzed using PMOD and Matlab software. Results: All organ time-activity curves without decay correction were normalized to the injected activity. The area under the normalized curves was then used to compute the dosimetry in each organ. The absorbed doses in mouse organs were computed using the Radiation Dose Assessment Resource animal models for dose assessment. Moreover, the addition of PG polysaccharides can significantly improve the dosimetry of GA in the lungs, and its effect was related to the administration time. Conclusions: Whole-body mouse imaging opens up a new avenue for the application of drug interactions between the TCMs.